Study on metabolic response of female and male Trogoderma varia-bile (Ballion) on different host grain using direct immersion solid-phase microextraction coupled with gas chromatography mass - Al-Shuwaili, Thamer; Mohammadali, Mushtak Talib; Lahuf, Adnan A.; Agarwal, Manjree; Koli, Pushpendra (Journal of Kerbala for Agricultural Sciences, 2024)
The purpose of this study is to use the technique of gas chromatography coupled with mass spectrometry to study the metabolite profile of Trogoderma variabile using different host grains including canola, oats, wheat, and barley. Also, hydrocarbon profiling can be used as a chemo-taxonomical tool for insect species identification, especially for very morphologically similar species like T. granarium. For sample preparation insects were subjected to extraction with acetonitrile. Direct Immersion-Solid Phase Microextraction (DI-SPME) was employed, followed by Gas Chromatography-Mass Spectrometry analysis (GC-MS) for the collection, separation, and identification of compounds. Additionally, insect host grains have a significant effect on the insect chemicals that are identified from T. variabile adults such as fatty acid and hydrocarbons. Results showed that insect host grains have a significant influence on the chemical compounds that are identified in females and males. There were twenty-three compounds were identified from adults reared on canola and wheat. However, there were 26 and 28 compounds detected from adults reared on oats and barley respectively. Results also showed that 11-methylpentacosane; 13-methylheptacosane; heptacosane; docosane, 1-iodo- and nonacosane were the most significant compounds that identified form T. variabile male reared on different host grains. However, the main compounds identified from female cultured on different host grains include docosane, 1-iodo-; 1-butylamine, N-butyl-; oleic acid; heptacosane; 13-methylheptacosane; hexacosane; nonacosane; 2-methyloctacosane; n-hexadecanoic acid and docosane in the female samples.